2006
DOI: 10.1177/153537020623100407
|View full text |Cite
|
Sign up to set email alerts
|

The Saponin-Mediated Enhanced Uptake of Targeted Saporin-Based Drugs is Strongly Dependent on the Saponin Structure

Abstract: Saponins are a group of plant glycosides consisting of a steroid or triterpenoid aglycone to which one or more sugar chains are attached. They exhibit cell membrane-permeabilizing properties and, thus, have been investigated for their therapeutic potential. Recently, at a non-permeabilizing concentration saponinum album from Gypsophila paniculata L. has been described to enhance the cytotoxicity of a chimeric toxin in a cell culture model. To elucidate whether this enhancing effect is also mediated by other sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 35 publications
(30 reference statements)
3
51
0
Order By: Relevance
“…The TTs were used in final concentrations ranging from 0.3 to 100 nM on NIH-3T3 cells and 0.03 to 10 nM on HER14 cells. For experiments using Saponinum album (Spn), a saponin composite from Gypsophila paniculata L., as enhancer for the specific cytotoxicity of saporin-based TTs, the cells were preincubated for 5 min as described (Bachran et al 2006). In these experiments the TTs were used in final concentrations ranging from 0.03 to 10 nM on NIH-3T3 cells and 0.03 to 10 pM on HER14 cells.…”
Section: Cytotoxicity Of Se Rrmentioning
confidence: 99%
“…The TTs were used in final concentrations ranging from 0.3 to 100 nM on NIH-3T3 cells and 0.03 to 10 nM on HER14 cells. For experiments using Saponinum album (Spn), a saponin composite from Gypsophila paniculata L., as enhancer for the specific cytotoxicity of saporin-based TTs, the cells were preincubated for 5 min as described (Bachran et al 2006). In these experiments the TTs were used in final concentrations ranging from 0.03 to 10 nM on NIH-3T3 cells and 0.03 to 10 pM on HER14 cells.…”
Section: Cytotoxicity Of Se Rrmentioning
confidence: 99%
“…be enhanced by lysosomotropic agents like chloroquine 203 or by saponins that accumulate in endosomal membranes, 204,205 but interference with cellular processes may also lead to artifacts when these methods are used in cell physiological studies. Very recently, the PE translocation domain was successfully used in a tripartite construct.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…They are glycosides with distinctive foaming characteristics and are natural detergents found in certain plants (Ajali, 2004). Saponins consist of a sugar moiety usually containing glucose, galactose, glucoronic acid, xylose, rhamnose or methylpentose, glycosidically linked to a hydrophobic aglycone (sapogenin) which may be triterpenoid or steroid in nature (Bachram et al, 2006;Unakalamba et al, 2013). A study done by Akinnuga et al (2011) reported similar findings but for different plant species, Gongronema latifolium, that the presence of saponin in leaf extract of the plant significantly reduced all blood cells by suppressing the haematopoiesis system.…”
Section: Discussionmentioning
confidence: 99%